Teacher Work Stress And Workload In East Sumba: Examining The Role Of Interpersonal And Environmental Factors - Rohisnawati; Matulessy, Andik; Rini, Amanda Pasca (International Conference on Sustainable Health Promotion, 2023)
Teacher work stress is an aspect of concern in today’s teacher resource management. This is because the teacher’s work environment is one of the factors that influence the stress of the teacher’s life. The purpose of this research is to analyze more deeply about the sources or factors of teacher work stress. This study used a quantitative method with a descriptive correlational type of research aimed at obtaining an overview of the variables studied and determining whether or not the influence of the three variables was involved. The participants in this study were 117 teachers. Sampling technique with quota sampling. The results of the study obtained a significance value of 0.000 < 0.05 and the calculated F value of 10.402 > F table 3.07, so there is a correlation between workload and organizational support for teacher work stress, with a confidence level of 15.4%. This means that the heavier the teacher’s workload, the higher the work stress experienced by the teacher and vice versa, the lighter the workload experienced by the teacher, the lighter the work stress experienced by the teacher. And the greater the support provided by the organization, the lighter the stress experienced by the teacher, and vice versa, the more there is no support provided by the organization, the greater the work stress experienced by the teacher.